Pengaruh beban kerja perceived organizational support dan work life balance sebagai prediktor turnover intention di cv tirta fertindo pratama - Wardono, Tino Indra; Supriyadi, Andhi; Nugraheni, Krisnawati Setyaningrum (Owner : Riset dan Jurnal Akuntansi, 2024)
Examining the problems in CV Tirta Fertindo Pratama, which has a high employee turnover rate so this research was conducted. This study uses a quantitative approach with four variables: Workload, Perceived Organizational Support and Work Life Balance are independent variables, while Turnover intention is the dependent variable. All employees of CV Tirta Fertindo Pratama, a total of 119 people, were used as respondents in this study. This study shows that each independent variable affects its dependent variable. The decision was: (1) workload has an influence on turnover intention, meaning more workload can make turnover intention increase; (2) Perceived Organizational Support has an influence on turnover intention, meaning more organizational support will reduce turnover intention; and (3) Work-life balance has an effect on turnover intention, meaning that more life balance will reduce turnover intention. (4) Workload, Perceived Organizational Support and work life balance simultaneously have an influence on turnover intention